Sustainable EOQ Model with Multi Container Transportation Problems - Ahmad Mubin; Fahmi Syahril; Tyas Yuli Rosiani (Jurnal Teknik Industri, 2021)
Industrial developments and environmental problems encourage decision-makers to determine optimal decisions. In addition, transportation is an aspect that has a significant contribution to environmental damage. Therefore, inventory and transportation decisions need to be integrated to minimize environmental problems. This study made an effort to develop a model of Sustainable EOQ with Multi Container Transportation Problems. The optimal procedure was proposed to determine the optimal number of containers in one vehicle. The results suggested that the proposed procedure could minimize the total annual inventory cost compared to the company's current solution.